Progressive Image Transmission by Segmentation-Based Coding - Caron, S.; Rivest, J.-F. (Journal of visual communication and image representation, 1996)
This paper presents a new Progressive Image Transmission methodology. It is based on a morphological segmentation technique: the watershed transformation, which is used to create a fine partition of the image. This partition is simplified by merging weakly contrasted regions. The methodology transmits high-contrast edges first, which is more appropriate to the human visual system. A comparison of the method with JPEG is done on human subjects, showing a significant performance improvement in image recognition times.